Determinasi Lingkungan Kerja dan Komitmen Organisasi terhadap Kinerja Karyawan PT. Sinar Niaga Sejahtera Sidoarjo - Putri Amalia Rulysca (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Improved employee performance will give an impact on the progress positively of every organization to survive in an unstable business environment competition. PT. Sinar Niaga Sejahtera Sidoarjo has few problems surrounding the work environment and organizational commitment that is feared to give an effect on the performance of its employees. This quantitative study was conducted on 100 employees of PT. Sinar Niaga Sejahtera Sidoarjo in 2019. Multiple linear regression was used to analyze all data among the study. To make certain about the result of the environment of work and commitment of organization on the performance of employees at PT. Sinar Niaga Sejahtera Sidoarjo was the principal intention of this study. As an outcome, the environment of work and commitment of organization shows a significant positive effect on the performance of employees, partially and simultaneously. It is recommended that management needs to maintain a conducive environment of work nowadays and commitment of organization that has been a stick in the employees. Also, things that need to be improved are providing a canteen or break room for employees, motivating employees with an individual approach or by giving equal rewards for their work which are making the small possibility of them leaving the organization and doing more detailed supervision of the work processes of their employees that will make them less likely to act outside procedure and not following orders from management. Instead, further research can add responses from other variables, such as compensation and employee motivation.